High-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material and preparation method thereof

By preparing nickel-supported reduced graphene oxide and combining it with external field-assisted composite and multi-stage deformation heat treatment, the problems of graphene dispersion and interfacial bonding in copper matrix were solved, and a copper-based composite material with high strength and high conductivity was realized.

CN121380666AActive Publication Date: 2026-01-23HENAN UNIV OF SCI & TECH

Patent Information

Application Number
CN202511960549.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-01-23
Estimated Expiration
2045-12-24

AI Technical Summary

Technical Problem

In existing technologies, graphene exhibits poor dispersion in copper matrices, tends to agglomerate, and has weak interfacial bonding, making it difficult to achieve a balance between strength and conductivity.

Method used

By preparing nickel-supported reduced graphene oxide and combining it with external field-assisted composite and multi-stage deformation heat treatment processes, uniform dispersion and strong interfacial bonding of graphene in a copper matrix are achieved, and its orientation alignment is controlled.

Benefits of technology

The prepared composite material has a tensile strength of over 700 MPa and an electrical conductivity of over 80% IACS, achieving an excellent combination of high strength and high conductivity, with good performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FZYOISNJ51U9MJIUDLWUBXQSN9TSM8OSJZWZMPCR
    Figure FZYOISNJ51U9MJIUDLWUBXQSN9TSM8OSJZWZMPCR
Patent Text Reader

Abstract

The invention discloses a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material and a preparation method thereof, and belongs to the technical field of metal-based composite materials. The method comprises the following steps: firstly, preparing nickel-loaded reduced graphene oxide powder, then atomizing the nickel-loaded reduced graphene oxide powder, adding the atomized nickel-loaded reduced graphene oxide powder into a copper melt, and applying a synergistic effect of an alternating magnetic field and a direct-current electric field to realize enhanced phase directional alignment and interface strengthening; and finally, through homogenizing annealing, circular machining of'multi-pass cold drawing deformation and intermediate annealing ', rotary swaging and low-temperature aging treatment, the composite material which is uniform in structure and tight in interface bonding is obtained. The material has high strength and high conductivity, the tensile strength of the material is not lower than 700 MPa, the conductivity of the material is not lower than 80% IACS, and the material is suitable for high-requirement electrical materials and electronic interconnection and aerospace conductor components.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of copper-based composite materials, in particular to a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material and a preparation method thereof. BACKGROUND

[0002] Copper and its alloys are widely used in power electronics, heat dissipation and interconnection materials due to their excellent electrical conductivity, thermal conductivity and processability. However, traditional Cu alloy materials have an inverted relationship between strength and electrical conductivity, that is, by alloying or work hardening to improve strength, the electrical conductivity is often significantly sacrificed. This contradiction limits its application in the field of high-end electrical materials, electronic interconnection, rail transportation and aerospace conductor components that require high electrical conductivity and high strength.

[0003] In recent years, graphene has been considered as an ideal reinforcing phase for improving the performance of copper-based composite materials due to its extremely high intrinsic strength and excellent electron mobility. In theory, introducing graphene into the copper matrix is expected to simultaneously improve the strength and electrical conductivity of the material. However, several key challenges are faced in the actual preparation process: first, the dispersibility of graphene sheets in the copper matrix is extremely poor and easily agglomerates, leading to uneven distribution of the reinforcing phase; second, the physical and chemical properties of graphene and copper are greatly different, resulting in poor interface wettability, weak interface bonding, and easy interface debonding under stress; third, the structure of graphene is easily damaged in traditional high-temperature smelting processes; finally, it is difficult to effectively control the orientation of graphene sheets during subsequent plastic deformation processing to fully utilize their anisotropic reinforcing effect.

[0004] In the prior art, graphene / copper composites prepared by mechanical mixing or electrodeposition methods generally have weak interface bonding and uneven dispersion of graphene, leading to unstable material performance and limited performance improvement. Therefore, there is an urgent need in the field for a new preparation method that can achieve uniform dispersion of graphene in the copper matrix, form strong interface bonding, and control the orientation of graphene, to break through the bottleneck of copper-based composite materials that are difficult to achieve both high strength and high electrical conductivity. SUMMARY

[0005] The present application aims to overcome the shortcomings of the prior art and provide a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material and a preparation method thereof. The method effectively solves the problems of graphene dispersion, interface bonding and orientation control through innovative surface modification of the reinforcing phase, external field assisted compounding and multi-stage deformation heat treatment process.

[0006] The technical scheme adopted by the present application to solve the above technical problems is as follows: On the one hand, the present application provides a preparation method of a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material, comprising the following steps: (1) Preparation of sheet-like graphene oxide; (2) Preparation of nickel-supported reduced graphene oxide powder: The graphene oxide obtained in step (1) is dispersed in ethylene glycol solvent, and Ni-containing... 2+ Solution, stir, so that Ni 2+ The Ni adsorbed on the surface of graphene oxide is then heated to 120–200 °C to undergo a reduction reaction, reducing the graphene oxide to reduced graphene oxide. Simultaneously, the Ni adsorbed on the surface is also reduced. 2+ Nickel nanoparticles were generated by reduction, and after cleaning and drying, nickel-supported reduced graphene oxide powder was obtained, which was then sealed and stored for later use. (3) Smelting and composite: The pure copper block is placed in a vacuum smelting furnace for smelting to obtain copper melt; the nickel-loaded reduced graphene oxide powder obtained in step (2) is injected into the copper melt by gas jetting to form a composite melt, and an alternating magnetic field with a frequency of 10-50Hz and a magnetic induction intensity of 0.5-2T and a DC electric field with an intensity of 5-20V / cm are applied to the composite melt at the same time to make the nickel-loaded reduced graphene oxide powder oriented in the copper melt and enhance the interfacial bonding; (4) Molding and post-processing: The composite melt processed in step (3) is injected into a crystallizer with electromagnetic stirring function for casting to obtain an ingot; the ingot is subjected to the following steps in sequence to obtain a high-strength, high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material: (4.1) Homogenization annealing: carried out at 600-800℃ for 2-6 hours; (4.2) Alternating cycle processing of multi-pass cold drawing deformation and intermediate annealing: In multi-pass cold drawing deformation, the area reduction rate of each pass is 8% to 20%; the intermediate annealing is carried out at 200 to 350°C for 5 to 30 minutes; (4.3) Rotary forging: carried out at 100-250℃, with radial deformation of 8%-20% per pass and a total of 3-8 passes; (4.4) Low temperature aging: 0.5-4h at 200-350℃.

[0007] Further, in step (1), graphene oxide is prepared by the following method: graphite powder with a particle size of 20-60 μm is placed in a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1 to 1:1 and reacted at 55-80°C for 5-8 hours to obtain graphene oxide with carboxyl and hydroxyl functional groups on its surface.

[0008] Furthermore, in step (2), the obtained nickel-supported reduced graphene oxide powder is subjected to reduction annealing treatment before use. The specific method of reduction annealing treatment is as follows: it is carried out at 200-400℃ in H2 / Ar atmosphere to completely reduce the partially oxidized nickel nanoparticles during the cleaning and drying process to elemental nickel.

[0009] Further, in step (3), the pure copper block is put into a vacuum melting furnace, vacuum is extracted to 5×10 2 After 5×10 Pa, argon is filled to 0.05 MPa, and the temperature is raised to 1250-1350℃ for melting.

[0010] Further, in step (4), the casting process is carried out under an argon protective atmosphere, and when the composite melt liquid surface is 2 cm away from the upper edge of the crystallizer, electromagnetic stirring with a frequency of 5 Hz and a current of 100 A is started.

[0011] Further, in step (4.2), the multi-pass cold drawing deformation and intermediate annealing cycle process are repeated 2-5 times.

[0012] On the other hand, the present application provides a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material prepared by the above preparation method, and the tensile strength of the obtained composite material is not less than 700 MPa, and the electrical conductivity is not less than 80% IACS.

[0013] It should be noted that, for the convenience of description, "graphene oxide" is referred to as "GO" hereinafter, "reduced graphene oxide" is referred to as "rGO", and "nickel-loaded reduced graphene oxide" is referred to as Ni-rGO.

[0014] The application solves the key problems in the preparation of graphene / copper composite material through a series of specific process steps, from reinforcement phase modification, composite process control to subsequent deformation heat treatment. The mechanism mainly reflects in the following aspects: (1) Ni-rGO is prepared by chemical method. Nickel nanoparticles act as a "bridge" connecting rGO and copper matrix. Strong Ni-C bond can be formed between nickel and carbon, so that rGO is firmly combined. At the same time, nickel and copper have good mutual solubility and wettability, which can effectively promote the wetting of copper liquid to the surface of the reinforcing phase during the composite process, and realize the strong metallurgical bonding between the reinforcing phase and the copper matrix through the possible transition layer of Cu-Ni-C, which fundamentally overcomes the problem of weak interface bonding of traditional graphene / copper. (2) The application applies alternating magnetic field and direct current electric field in the composite melt. The Lorentz force generated by the alternating magnetic field makes the anisotropic Ni-rGO powder rotate and arrange along the magnetic field direction, thereby optimizing its reinforcing effect. The direct current electric field promotes the migration of electrons at the interface, which may activate the interface reaction and further enhance the chemical bonding between Ni-C-Cu. (3) The application precisely controls the microstructure through multi-stage deformation heat treatment process. The cycle process design of "multi-pass cold drawing deformation + intermediate annealing" realizes the balance between large deformation accumulation and structure relaxation. Multi-pass cold drawing deformation refines the copper matrix grain and further orients the GO layer along the cold drawing direction; short-time intermediate annealing releases processing stress, restores material plasticity, and protects the graphene structure from being damaged during severe deformation. The subsequent spinning process realizes further densification and interface compression at a lower temperature. The final low-temperature aging treatment helps to stabilize the deformed structure and may induce fine precipitation, which cooperatively improves the strength and stability.

[0015] Based on the above principles, the application has the following significant beneficial effects compared with the prior art: (1) In the Ni-rGO powder prepared by the application, the Ni nanoparticles act as an interface bridge and form a strong Ni-C bond with rGO, and form a good metallurgical bond with the copper matrix, effectively solving the problem of interface debonding of traditional graphene / copper composite materials, so that the stress can be efficiently transmitted from the matrix to the reinforcing phase.

[0016] (2) The application sprays the Ni-rGO powder into the copper melt by gas injection method, which effectively prevents the agglomeration of graphene. Especially in the alternating magnetic field applied during the composite process, the flaky Ni-rGO can be arranged in the direction of the magnetic field; the synergistic effect of the direct current electric field further promotes the interface reaction, so that a composite structure with uniform distribution of reinforcing phase and good orientation is obtained, reducing the anisotropy and instability of performance.

[0017] (3) Through electromagnetic stirring casting in the application, a ingot with uniform composition and dense structure is obtained. After subsequent multi-stage deformation heat treatment process, the strength is greatly improved, while micro-cracks and graphene damage caused by excessive processing are avoided, and high electrical conductivity is maintained.

[0018] (4) Through the synergy of each process, the composite material prepared by the application successfully breaks the inverted relationship between strength and electrical conductivity. The tensile strength of the material reaches more than 700MPa, and the electrical conductivity is maintained at more than 80% IACS, realizing the excellent combination of high strength and high conductivity, and good performance reproducibility.

[0019] (5) The preparation method of the application has clear steps and clear key process parameter ranges. By adjusting the cycle number of "multi-pass cold drawing deformation + intermediate annealing" and the spinning pass, the final performance of the material can be adjusted within a certain range to meet the needs of different application scenarios, and has good industrialization prospects. DETAILED DESCRIPTION

[0020] The technical solutions of the application will be described below in conjunction with specific embodiments. Obviously, the described embodiments are only some of the embodiments of the application, not all. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor are within the protection scope of the application.

[0021] The application provides a preparation method of a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material, which comprises the following steps performed in sequence: (1) Preparing flaky GO: placing graphite powder with a particle size of 20-60um in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1-1:1, and reacting at 55-80℃ for 5-8h to obtain flaky GO; this step forms carboxyl and hydroxyl functional groups on the surface of GO, enhancing its adsorption capacity for metal ions and subsequent interface bonding performance; (2) Preparing a Ni 2+ solution: dissolving NiCl2·6H2O in ethylene glycol to prepare a solution with a concentration of 10-30mg / mL, obtaining a uniform and stable Ni 2+ solution; in this step, ethylene glycol as a solvent can form a complex with Ni 2+ , preventing its hydrolysis and precipitation, and maintaining the stability of the solution; (3) Preparing a GO dispersion: dispersing the GO obtained in step (1) in ethylene glycol at a ratio of 1-3g GO per 50mL ethylene glycol, and ultrasonic treating at a frequency of 30kHz for 1-2h to obtain a uniformly dispersed GO dispersion; this step fully disperses the GO lamellas to avoid agglomeration; (4) Preparation of Ni-rGO powder: The Ni-containing GO dispersion obtained in step (2) was added into the GO dispersion of step (3) and stirred for 30-90 min, so that the Ni was adsorbed on the surface of GO, and then heated to 120-200°C for reduction reaction, so that the GO was reduced to rGO, and the surface-adsorbed Ni was reduced to nickel nanoparticles, obtaining Ni-rGO powder; this step realizes in-situ anchoring of nickel nanoparticles on the surface of rGO, forming an interface bridging structure; then the product was centrifuged and washed to remove residual ions and organic matter, and vacuum dried at 60-100°C under an inert atmosphere; 2+ 2+ 2+ (5) Reduction annealing and preservation: the Ni-rGO powder dried in step (4) was subjected to reduction annealing at 200-400°C under H2 / Ar atmosphere, and then sealed and preserved under an inert atmosphere or vacuum condition; this step completely reduces the possible oxidized nickel to metallic state, and further enhances the interface bonding between Ni and rGO; (6) Melting of copper: a pure copper block was placed in a vacuum melting furnace, vacuumed to 5x10 2 Pa, then argon was filled to 0.05 MPa, and heated to 1250-1350°C to obtain a copper melt; (7) Addition and dispersion of reinforcing phase: the Ni-rGO powder preserved in step (5) was sprayed into the copper melt of step (6) using a gas jet nozzle to obtain a composite melt; this step realizes rapid and uniform dispersion of the reinforcing phase in the copper melt, avoiding agglomeration; (8) Electromagnetic field synergistic treatment: an alternating magnetic field and a direct current electric field were simultaneously applied to the composite melt obtained in step (7); the frequency of the alternating magnetic field was 10-50 Hz, and the magnetic induction intensity was 0.5-2 T; the intensity of the direct current electric field was 5-20 V / cm; in this step, the alternating magnetic field made the Ni-rGO align along the magnetic field direction, and the direct current electric field promoted interface electron migration and chemical reaction, together enhancing the interface bonding; (9) Electromagnetic stirring casting: the composite melt treated in step (8) was poured into a crystallizer with electromagnetic stirring function, and when the melt surface was about 2 cm away from the upper edge of the crystallizer, electromagnetic stirring was started with a stirring frequency of 5 Hz and a current of 100 A, so that the melt was solidified under argon protection atmosphere to obtain a composite ingot with uniform structure and high density; this step further homogenizes the structure and reduces defects through electromagnetic stirring; (10) Post-treatment of the ingot: the ingot obtained in step (9) was subjected to the following treatments in sequence: (10.1) Homogenization annealing: annealing at 600-800°C for 2-6 h under argon or vacuum atmosphere to eliminate composition segregation and stabilize the interface structure; ​​​(10.2) Multi-pass cold drawing deformation: cold drawing deformation is performed on the ingot, with an area reduction of 8-20% per pass, to achieve preliminary deformation strengthening and orientation of rGO along the cold drawing deformation direction; (10.3) Intermediate annealing: annealing at 200-350°C in an argon or vacuum atmosphere for 5-30 min to restore material plasticity and maintain the integrity of the graphene structure; (10.4) Cycle processing: repeating steps (10.2)-(10.3) until the target deformation amount or mechanical property requirement is reached, to accumulate deformation, refine grains, and control orientation through the cycle process; (10.5) Rotary forging: rotary forging at 100-250°C, with a radial deformation of 8-20% per pass, and a total processing pass of 3-8 times, to further refine grains, eliminate pores, and improve interface bonding; (10.6) Low-temperature aging: aging at 200-350°C for 0.5-4 h to promote the formation of nano precipitates and improve material strength and microstructure stability; Through the above steps, the high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material (hereinafter referred to as "composite material") is finally obtained.

[0022] The technical solutions of the present application will be described clearly and completely below in conjunction with specific examples and comparative examples. Obviously, the described examples are only a part of the examples of the present application, rather than all the examples. Based on the examples in the present application, all other examples obtained by those skilled in the art without creative labor fall within the protection scope of the present application.

[0023] Example 1 The present example provides a preparation method of a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material, which specifically comprises the following steps: (1) Graphite powder with a particle size of 40 μm is placed in a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 2:1, and reacted at 60°C for 6 h to obtain flaky GO; (2) NiCl2·6H2O is dissolved in ethylene glycol to prepare a Ni 2+ containing solution with a concentration of 20 mg / mL; (3) 2 g of GO prepared in step (1) is dispersed in 100 mL of ethylene glycol, and ultrasonically treated at 30 kHz for 1.5 h to obtain a GO dispersion; (4) The Ni 2+ containing solution of step (2) is added to the GO dispersion of step (3), stirred for 60 min, and then heated to 160°C for 2 h. After the reaction, the product is centrifuged, washed with deionized water and ethanol alternately, and vacuum dried at 80°C to obtain Ni-rGO powder; (5) The dried Ni-rGO powder of step (4) was reduced annealed at 300℃ for 1h under H2 / Ar (volume ratio 1:9) atmosphere, and then sealed and stored; (6) The pure copper block was placed in a vacuum melting furnace, vacuumed to 5x10 2 After 5 Pa, argon was filled to 0.05 MPa, and the temperature was raised to 1300℃ for melting, to obtain a copper melt; (7) The Ni-rGO powder prepared in step (5) (added amount of 0.5% of the mass of copper) was sprayed into the copper melt using an argon gas atomizing nozzle to form a composite melt; (8) An alternating magnetic field with a frequency of 30 Hz and a magnetic induction intensity of 1.5 T and a direct current electric field with a strength of 12 V / cm were applied to the composite melt at the same time for 10 min; (9) The composite melt was poured into a crystallizer with electromagnetic stirring function, and electromagnetic stirring (frequency 5 Hz, current 100 A) was started when the liquid surface was 2 cm from the upper edge, and the ingot was obtained by solidification under argon protection; (10) The ingot was subjected to the following post-processing: (10.1) Homogenization annealing at 750℃ for 4h under argon protection; (10.2) 3 passes of cold drawing deformation, with a cross-sectional reduction of about 10% for each pass; (10.3) After cold drawing deformation, intermediate annealing at 250℃ under argon protection for 20 min; (10.4) Repeat steps (10.2) to (10.3) for a total of 3 cycles; (10.5) Spinning at 180℃, with a radial deformation of about 12% for each pass, a total of 5 times; (10.6) Low-temperature aging treatment at 300℃ under argon protection for 1h to obtain the final composite material.

[0024] Example 2 The difference between this example and Example 1 is only that in step (10.4), the number of cycles of cold drawing deformation and intermediate annealing is 2.

[0025] Example 3 The difference between this example and Example 1 is only that in step (10.4), the number of cycles of cold drawing deformation and intermediate annealing is 5.

[0026] Example 4 The difference between this example and Example 1 is only that in step (10.5), the spinning parameters are adjusted to a radial deformation of about 15% for each pass, with a total of 5 passes.

[0027] Example 5 The difference between this example and Example 1 is only that in step (10.5), the spinning parameter is adjusted to a radial deformation of about 10% per pass, and the total number of passes is 7.

[0028] Comparative Example 1 The difference between this comparative example and Example 1 is only that in step (1), the preparation reaction temperature of GO is 40℃.

[0029] Comparative Example 2 The difference between this comparative example and Example 1 is only that in step (1), the preparation reaction temperature of GO is 90℃.

[0030] Performance test and result analysis The composite material samples prepared in Examples 1-5 and Comparative Examples 1-2 above were subjected to performance tests, including hardness, electrical conductivity and tensile properties.

[0031] Among them, the hardness test used a HVS-1000 type Vickers hardness tester, a load of 500g, a pressure holding time of 10s, and 10 different points on the surface of each sample were tested to take the average value. The electrical conductivity test used a Sigma 2008B1 type digital conductivity meter to test the electrical conductivity at room temperature, and the results were expressed as a percentage relative to the International Annealed Copper Standard (IACS). The tensile property test used an AG-I-250kN electronic universal testing machine to perform room temperature tensile test to test the tensile strength. The test results are shown in Table 1.

[0032] Table 1 Performance test results of samples in Examples 1-5 and Comparative Examples 1-2 The data in Table 1 show that the composite materials prepared by the method of the present application in the range of the provided process parameters (Examples 1-5) all successfully achieve the application target of tensile strength exceeding 700 MPa and electrical conductivity higher than 80% IACS, embodying the stability and reliability of the process. Among them, Example 1 as an example of optimized parameters, exhibits the best comprehensive performance matching. The specific analysis is as follows: the number of cycles of "multi-pass cold drawing deformation + intermediate annealing" is one of the key parameters for regulating performance, and 2 cycles (Example 2) can already make the material meet the requirements, and 3 cycles (Example 1) further realizes a more optimal balance of strength and conductivity; 5 cycles (Example 3) demonstrates that by increasing the number of cycles, the performance balance can be flexibly adjusted while maintaining high strength. The spinning process is also adjustable, and the parameter combination of Example 1 (12% deformation each time, 5 times) achieves the best effect, while Examples 4 and 5 show that by adjusting the single deformation amount and pass, the performance can be fine-tuned within a certain range. The results of Comparative Examples 1 and 2 on the other hand prove that the GO preparation temperature needs to fall within the range of 55-80°C defined by the present application, and exceeding this range will result in a decline in interface quality and overall performance. In summary, through the synergistic process system of "Ni-rGO reinforcing phase preparation - electromagnetic field assisted compounding - multi-stage deformation heat treatment", especially the optimized parameter combination as shown in Example 1, the present application can stably prepare composite materials with performance far exceeding that of the comparative examples, effectively solving key technical problems such as reinforcing phase dispersion, interface bonding and performance inversion.

[0033] The above provides a detailed introduction to a high-strength and high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material and a method for preparing the same. In this paper, specific examples are applied to explain the principles and specific implementation modes of the present application. The above examples are only used to help understand the method and core idea of the present application. It should be noted that for ordinary skilled persons in the art, any simple modification, equivalent change and modification made according to the technical essence of the present application to the above examples all fall within the protection scope of the present application.

Claims

1. A method for preparing a high-strength, high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material, characterized in that, Includes the following steps: (1) Preparation of sheet-like graphene oxide; (2) Preparation of nickel-supported reduced graphene oxide powder: The graphene oxide obtained in step (1) is dispersed in ethylene glycol solvent, and Ni-containing... 2+ Solution, stir, so that Ni 2+ The Ni adsorbed on the surface of graphene oxide is then heated to 120–200 °C to undergo a reduction reaction, reducing the graphene oxide to reduced graphene oxide. Simultaneously, the Ni adsorbed on the surface is also reduced. 2+ Nickel nanoparticles were generated by reduction, and after cleaning and drying, nickel-supported reduced graphene oxide powder was obtained, which was then sealed and stored for later use. (3) Smelting and composite: The pure copper block is placed in a vacuum smelting furnace for smelting to obtain copper melt; the nickel-loaded reduced graphene oxide powder obtained in step (2) is injected into the copper melt by gas jetting to form a composite melt, and an alternating magnetic field with a frequency of 10-50Hz and a magnetic induction intensity of 0.5-2T and a DC electric field with an intensity of 5-20V / cm are applied to the composite melt at the same time to make the nickel-loaded reduced graphene oxide powder oriented in the copper melt and enhance the interfacial bonding; (4) Molding and post-processing: The composite melt processed in step (3) is injected into a crystallizer with electromagnetic stirring function for casting to obtain an ingot; the ingot is subjected to the following steps in sequence to obtain a high-strength, high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material: (4.1) Homogenization annealing: carried out at 600-800℃ for 2-6 hours; (4.2) Alternating cycle processing of multi-pass cold drawing deformation and intermediate annealing: In multi-pass cold drawing deformation, the area reduction rate of each pass is 8% to 20%; the intermediate annealing is carried out at 200 to 350°C for 5 to 30 minutes; (4.3) Rotary forging: carried out at 100-250℃, with radial deformation of 8%-20% per pass, and a total of 3-8 processing passes; (4.4) Low temperature aging: 0.5-4h at 200-350℃.

2. The preparation method according to claim 1, characterized in that, In step (1), graphene oxide is prepared by the following method: graphite powder with a particle size of 20-60 μm is placed in a mixture of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 3:1 to 1:1 and reacted at 55-80℃ for 5-8 hours to obtain graphene oxide with carboxyl and hydroxyl functional groups on its surface.

3. The preparation method according to claim 1, characterized in that, In step (2), the obtained nickel-supported reduced graphene oxide powder is subjected to reduction annealing treatment before use. The specific method of reduction annealing treatment is as follows: it is carried out at 200-400℃ in H2 / Ar atmosphere to completely reduce the nickel nanoparticles partially oxidized during the cleaning and drying process to elemental nickel.

4. The preparation method according to claim 1, characterized in that, In step (3), the pure copper block is placed in a vacuum melting furnace and evacuated to a vacuum level of 5×10. 2 After Pa, argon gas is introduced to 0.05 MPa, and the temperature is raised to 1250-1350℃ for melting.

5. The preparation method according to claim 1, characterized in that, In step (4), the casting process is carried out under an argon protective atmosphere, and when the surface of the composite melt is 2 cm from the upper edge of the crystallizer, an electromagnetic stirrer with a frequency of 5 Hz and a current of 100 A is started.

6. The preparation method according to claim 1, characterized in that, In step (4.2), the cyclic processing of multiple cold drawing deformation and intermediate annealing is repeated 2 to 5 times.

7. A high-strength, high-conductivity nickel-loaded reduced graphene oxide reinforced copper-based composite material prepared by the preparation method according to any one of claims 1-6, characterized in that, The resulting composite material has a tensile strength of not less than 700 MPa and an electrical conductivity of not less than 80% IACS.

Citation Information

Patent Citations

  • Multi-mold cold-rotary-swaging and cold-drawing machining method for AgSnO2 wire rods

    CN107052075A

  • Grapheme-reinforced copper-based composite material and jetting formation method thereof

    CN107988513A

  • Preparation method of graphene reinforced copper-based composite material

    CN111451491A

  • Preparation method of magnetic field-electric field synergistically driven Fe3O4-loaded graphene three-dimensional interlocking network / metal composite material

    CN120719158A

  • Efficient microwave preparation method with one-step simultaneous reduction / embedding and application of metal monatomic-doped reduced graphene oxide dielectric material

    US20240174518A1

Cited By

  • Graphene / nickel-cobalt bimetallic oxide / PMI foam composite wave-absorbing material and preparation method and repairing method thereof

    CN121628571A